Identifying ignitable liquids in fire debris : a guideline for forensic experts /: a guideline for forensic experts. ([2016]) - Hendrikse, Jeanet; Grutters, Michiel; (Of Germany. Bundeskriminalamt), Schäfer, Frank
No abstract available